EKSPLORASI TIKTOK SEBAGAI MEDIA PEMBELAJARAN: ANALISIS KONTEN TIKTOK @marhaban.academy DENGAN KURIKULUM MERDEKA - Kyla Raissa; Tatang Tatang; Mia Nurmala (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The TikTok application is increasingly being used as an alternative learning medium, including for Arabic language learning. However, Arabic language learning content on TikTok is not necessarily aligned with the current curriculum, potentially failing to support learning needs in schools. Therefore, this study aims to analyze the suitability of Arabic language learning content on the TikTok account @marhaban.academy with the Arabic Language Learning Outcomes (CP) for Phase F of the Merdeka Curriculum, which comprises two main components: language skills (maharah) and essential material related to daily life. The method employed is content analysis with a descriptive qualitative approach, following Klaus Krippendorff's analytical stages and utilizing Fenwick W. English's (1992) Curriculum Alignment Theory framework as a benchmark for determining suitability. The classification into